2017
DOI: 10.3390/su9122323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Regulation Stringency on the Pulp and Paper Industry

Abstract: Abstract:The article investigates whether environmental regulations have affected productivity development and technological change in the European pulp and paper industry. A dynamic panel data approach is selected for analyzing a sample consisting of the pulp and paper industries in eight European countries. Industry total factor productivity for the period 1993-2009 is used as the dependent variable; it is explained by the intensities of environmental regulations for various types of pollutants, as well as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 73 publications
0
13
1
Order By: Relevance
“…Related empirical applications, using plant-level data, exist also for the Nordic countries [79,80,81•], some focusing on TFP development and others on changes in profitability. Another strand of research has employed aggregate data at the industry level for EU Member States [82,83]. The results are overall mixed, some suggesting that there is negative relationship between existing regulations and productivity/profits (e.g., [79,82]) while others report a corresponding positive (or non-significant) relationship [81,83].…”
Section: Environmental Regulation and Productivitymentioning
confidence: 99%
“…Related empirical applications, using plant-level data, exist also for the Nordic countries [79,80,81•], some focusing on TFP development and others on changes in profitability. Another strand of research has employed aggregate data at the industry level for EU Member States [82,83]. The results are overall mixed, some suggesting that there is negative relationship between existing regulations and productivity/profits (e.g., [79,82]) while others report a corresponding positive (or non-significant) relationship [81,83].…”
Section: Environmental Regulation and Productivitymentioning
confidence: 99%
“…Studies in the literature show mixed results. Some of them indicate that there is a strong negative relationship between government's environmental regulation and firm's financial performance, while others hint at a possibility of a positive relationship [14][15][16][17][18]. For instance, Sueyoshi and Goto (2009) found that the environmental protection expenditure of US electric utility firms decreased their financial performance [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They further put forth that if they carry out the analysis through a dynamic framework, which embraces the possibility of fostering innovation, then the firm could reduce its production cost [15]. Similarly, Al-Tuwaijri et al (2004) hinted that good environmental performance is significantly associated with good economic performance [16], while Brolund and Lundmark (2017) found that the regulation about environmental pollutants could drive firm's productivity improvements [17]. In a similar vein, Ashford and Hall (2011) suggested that the sustainable development requires stimulating revolutionary technological innovations through environmental, health, safety, economic, and labor market regulations [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies have found that the U.S. Clean Air Act, enacted in 1970, caused high structural unemployment in pollution-intensive industrial enterprises and a decline in capital stocks, economic growth rates, and total factor productivity (TFP) [2,3]. Gray and Shadbegian [4] analyzed the relationship between productivity, pollution abatement expenditures, and other measures of environmental regulation in plants across three industries, and they found that more-regulated plants had significantly lower productivity levels, and slower productivity growth rates than less-regulated plants. Compared with command-control environmental regulation, market-based measures that increased coal prices could effectively reduce coal usage and air pollution in India, but also hindered the entry of new enterprises and forced them to withdraw from the market [5].…”
Section: Introductionmentioning
confidence: 99%